(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
this article covers the improvement of the concepts of responsibility and commitment of enterprises producing basalt products in the satisfaction of demand and desire of their consumers and stakeholders, as well as in the achievement of their involvement in the provision of products and services. It is written that the organization and manufacturing enterprises make a strategic decision in applying a Quality Management System that can help improve the results of their activities and provide initiatives with a solid foundation, designed for Sustainable Development.